Abnormal Nerve Conduction Study Findings Indicating the Existence of Peripheral Neuropathy in Multiple Sclerosis and Neuromyelitis Optica. (7th November 2013) - Warabi, Yoko; Yamazaki, Mikihiro; Shimizu, Toshio; Nagao, Masahiro
Abstract : Objective . Chronic inflammatory demyelinating polyneuropathy (CIDP) has been reported in patients with multiple sclerosis (MS). However, there have been limited reports of peripheral neuropathy as a complication of neuromyelitis optica (NMO). In this paper, we showed the characteristics and differences between peripheral neuropathy as a complication of MS and NMO. Method . We analyzed a series of 58 MS and 28 NMO patients and evaluated nerve conduction studies (NCS) in 21 MS and 5 NMO patients. Results . Six of the 58 MS and 3 of the 28 NMO patients revealed abnormal NCS findings. Three (5.2%) of the 58 MS patients fulfilled the criteria for CIDP. One (3.6%) of the 28 NMO patients showed peripheral neuropathy at the same time of NMO relapse, although CIDP was not seen in NMO. The other 5 (3 MS and 2 NMO) patients were complicated with neuropathy caused by concomitant diabetes mellitus and Sjögren's syndrome. Conclusion . Frequency of abnormal NCS findings might exhibit no significant difference between MS and NMO, although the cause and pathophysiology of peripheral neuropathy were different in MS and in NMO. There might be a group of NMO who were affected simultaneously in the central and peripheral nervous tissues.